Assessing executive functions and metacognition: translational potential of the Metacognitive Wisconsin Card Sorting Test for developmental neuropsychology - Granato, Giovanni; Manzi, Giulia; Di Giulio, Jordy; Puzzo, Concetto; Mattera, Andrea; Adriani, Walter; Baldassarre, Gianluca; Capobianco, Micaela (Frontiers in Behavioral Neuroscience, 2025)
The development of metacognition and executive functions supports adaptive and goal-oriented behavior in adulthood. Therefore, effective screening of these skills is essential for implementing early interventions in educational and clinical settings. While neuropsychological tests usually focus on a single skill and require clinicians to use lengthy batteries, the Metacognitive Wisconsin Card Sorting Test (Meta-WCST) assesses metacognition, executive functions, and their interaction. However, this test has not yet been scientifically validated for children with either typical or atypical development. This gap highlights both a methodological shortcoming and a missed opportunity for developmental neuropsychology. In this review, we provide a comprehensive analysis of studies involving the Meta-WCST, aiming to evaluate its translational potential for developmental applications. Despite several methodological limitations in the current literature, our evaluation indicates that the Meta-WCST can be adapted to developmental contexts through targeted improvements to theoretical and computational frameworks, data analysis methods, and protocol procedures. These considerations have meaningful implications for multiple areas of developmental neuropsychology, including scientific research, educational practices, and clinical assessments.